EPR of Pentavalent Molybdenum in Liquid Solutions - Abraham, M. M.; Abriata, José Pablo; Foglio, M. E.; Pasquini, E. (Elsevier BV, 1966)
Fil: Abraham, M. M. Comisión Nacional de Energía Atómica; Argentina